Implementation of Regulation of the Minister of Transportation Number 45 of 2020 on the Use of Electric Bicycles on Highways in Cirebon Regency - Syahputra, Argia; Fadhillah, Ilyas; Saputra, Guntur Wahyu; Gunawan, M. Sigit; Dimyati, Agus (Jurnal Legisci, 2025)
Background. The rise of the use of electric bicycles on the highways of Cirebon Regency has caused unrest among other road users, mainly due to the difference in speed, the use of inappropriate lanes, and the absence of engine noise that often surprises other motorists. To regulate this, the Minister of Transportation issued Regulation of the Minister of Transportation (Permenhub) No. 45 of 2020 concerning Certain Vehicles Using Electric Motor Drives, which regulates technical requirements, lanes, and the minimum age of electric bicycle users, as well as requiring the use of helmets and other safety equipment. However, the Regulation has not been able to solve the above problems due to the lack of thorough socialization, which leads to a lack of public understanding of the applicable regulations and the lack of supporting infrastructure. The purpose of the research is to provide the public with an understanding of the regulations and technical rules for using electric bicycles. Aims. This study formulates a problem regarding how to implement Permenhub No. 45 of 2020 on the use of electric bicycles on the highways of Cirebon Regency. Methods. Using an empirical juridical research method, this study shows that regulation implementation is still not optimal. It is characterized by low public awareness of the rules, limited infrastructure, and the absence of derivative regulations at the regional level. Conclusion. In conclusion, the effectiveness of Permenhub No. 45 of 2020 in Cirebon Regency is influenced by factors such as a lack of socialization, a lack of supporting facilities, and weak law enforcement, so collaborative efforts are needed between the local government and the community to create safer and more orderly traffic